2018
DOI: 10.1155/2018/4608490
|View full text |Cite
|
Sign up to set email alerts
|

Nail Involvement in Patients with Psoriatic Arthritis in Northern Iran

Abstract: Background Psoriatic arthritis (PsA) results in an increased burden of psoriasis and impairs both quality of life and an individual's functional capacity. The relationship between nail involvement and PsA in psoriasis is not fully characterized. Aim To evaluate the frequency and characteristics of nail involvement in psoriatic patients and to assess the relationship with joint involvement. Methods A total of 197 patients with moderate-to-severe psoriasis were consecutively invited to participate in this cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
6
1
2
Order By: Relevance
“…The prevalence of nail involvement in our study population is lower than that observed in previous real-world studies of patients with varied prior biologic experience, which have reported rates of nail involvement ranging from 50% to 87% among patients with PsA. (33)(34)(35)(36)(37)(38)(39) Notably, approximately 31% of patients in our study population had received biologic therapy and 29% had received conventional synthetic disease-modifying antirheumatic drugs prior to enrollment, which may have ameliorated nail disease in those patients before their participation in the study. (5,26) Additionally, the majority of previous studies specifically enrolled patients with PsA and psoriasis, whereas the presence of psoriasis was not a criterion for enrollment in our study.…”
Section: Discussioncontrasting
confidence: 58%
“…The prevalence of nail involvement in our study population is lower than that observed in previous real-world studies of patients with varied prior biologic experience, which have reported rates of nail involvement ranging from 50% to 87% among patients with PsA. (33)(34)(35)(36)(37)(38)(39) Notably, approximately 31% of patients in our study population had received biologic therapy and 29% had received conventional synthetic disease-modifying antirheumatic drugs prior to enrollment, which may have ameliorated nail disease in those patients before their participation in the study. (5,26) Additionally, the majority of previous studies specifically enrolled patients with PsA and psoriasis, whereas the presence of psoriasis was not a criterion for enrollment in our study.…”
Section: Discussioncontrasting
confidence: 58%
“…One of the limitations of the present investigation was the lack of control group to compare the rate of onychomycosis in psoriatic patients and control population; nevertheless, the majority of fungal infections in our study belonged to the nail infections (52.2%). is is less than the nail involvement reported by Jendoubi et al [28] and Zargari et al [29] which were 71.2% and 69.5%, respectively. In line with our findings, nail pitting is the most common nail matrix involvement among psoriatic patients [30].…”
Section: Discussionmentioning
confidence: 50%
“…The study by Zargari O et al showed a significant correlation between the psoriasis severity and the NAPSI scores. They also found a fall in PASI and NAPSI scores following treatment, though NAPSI scores fell at a slower rate [23] . The most frequent nail finding was pits seen in 43 patients (93%) followed by Onycholysis, Leukonychia, crumbling of nail Plate, and least were Splinter hemorrhage, Red spots in lunula and Beau's lines.…”
Section: Discussionmentioning
confidence: 94%